Fluorescently-labeled fremanezumab is distributed to sensory and autonomic ganglia and the dura but not to the brain of rats with uncompromised blood brain barrier. (March 2020) - Noseda, Rodrigo; Schain, Aaron J; Melo-Carrillo, Agustin; Tien, Jason; Stratton, Jennifer; Mai, Fanny; Strassman, Andrew M; Burstein, Rami
Background: The presence of calcitonin gene-related peptide and its receptors in multiple brain areas and peripheral tissues previously implicated in migraine initiation and its many associated symptoms raises the possibility that humanized monoclonal anti-calcitonin gene-related peptide antibodies (CGRP-mAbs) can prevent migraine by modulating neuronal behavior inside and outside the brain. Critical to our ability to conduct a fair discussion over the mechanisms of action of CGRP-mAbs in migraine prevention is data generation that determines which of the many possible peripheral and central sites are accessible to these antibodies – a question raised frequently due to their large size. Material and methods: Rats with uncompromised and compromised blood-brain barrier (BBB) were injected with Alexa Fluor 594-conjugated fremanezumab (Frema594), sacrificed 4 h or 7 d later, and relevant tissues were examined for the presence of Frema594. Results: In rats with uncompromised BBB, Frema594 was similarly observed at 4 h and 7 d in the dura, dural blood vessels, trigeminal ganglion, C2 dorsal root ganglion, the parasympathetic sphenopalatine ganglion and the sympathetic superior cervical ganglion but not in the spinal trigeminal nucleus, thalamus, hypothalamus or cortex. In rats with compromised BBB, Frema594 was detected in the cortex (100 µm surrounding the compromised BBB site) 4 h but not 7 d after injections. Discussion: Our inability to detect fluorescent (CGRP-mAbs) in the brain supports the conclusion that CGRP-mAbs prevent the headache phase of migraine by acting mostly, if not exclusively, outside the brain as the amount of CGRP-mAbs that enters the brain (if any) is too small to be physiologically meaningful.